Overview of lower urinary tract symptoms post-trauma intensive care unit admission - Emmanuel Owusu Sekyere; Timothy Craig Hardcastle; Ronisha Sathiram; Boikhutso Tlou (African Journal of Urology, 2020)
Abstract Background The study was undertaken to assess the incidence of lower urinary tract symptoms (LUTS) after short-term indwelling urethral catheter (IUC) in polytrauma patients admitted to a level one trauma unit using core lower urinary tract symptom score (CLSS). Data of patients admitted between January 2013 and December 2015 and meeting the study criteria were retrieved from the hospital informatics system. Chart review was done, and patients were subsequently interviewed telephonically. Results Ninety-four respondents comprising of 81.9% males and 18.1% females out of the 221 eligible patients were contacted. The most common LUTS reported was urethral pain, and 90% had mild to moderate symptoms. No severe LUTS were identified. There was a positive correlation between the duration of IUC and LUTS, but there was no statistically significant association between age and LUTS in our study population. Conclusion Short-term duration of IUC in the trauma ICU patient is associated with predominantly mild irritative LUTS which are mostly self-limiting and may not need further investigations and management. CLSS was found to be a useful screening tool. Further studies are needed to confirm findings in our study.